Effect of adding water extract of Syzigium aromaticum to drinking water in the microbial characteristics of broiler intestines - Zaman K.F. AL-Mhsenawi; Majid H.A. Al-Asadi; Sabah K.M. AL- hummod; Ali M. Al-Aboudi (Zien Journals, 2023)
This study was aim to determine the microbial content in the intestines of broilers treated with water extract of carnation flowers for drinking water, represented by the logarithmic numbers of intestinal and colon bacteria, 180 broiler chicks Ross308 were used, distributed randomly into four treatments, each treatment consisted of 45 chicks, with three replicates per treatment and 15 chicks per replicate. The experimental treatments comprised of four groups: T1, which served as the control treatment without any addition, T2, T3, and T4: adding water extract of carnation flowers at a rate of 200, 300 and 400 ml / liter of drinking water, respectively. Measurements were taken at the fifth week. According to the results, the addition treatments showed a significant decrease (P≤0.05) in the numbers of total aerobic bacteria and coliform bacteria when compared to the control treatment, the percentage of the decrease with the increase in the percentage of addition of the extract, with a significant increase (P≤0.05) in the numbers of anaerobic bacteria Lactobacilli bacteria for the addition treatments compared to the control treatment, the percentage of rise increases with the increase in the percentage of addition of the extract compared to the control treatment.
Keywords: microbial characteristics; broiler intestiens